RETRACTION NOTE: Histopathological and biomedical parameters determination in the protective effect of crocin on hepatotoxicity induced by methotrexate in rats - Cyrus Jalili; Amir Abdolmaleki; Shiva Roshankhah; Mohammad Reza Salahshoor (Journal of HerbMed Pharmacology, 2022)
This paper was published in the Journal of Herbmed Pharmacology in 2020 (doi: 10.15171/jhp.2020.07) (1). Based on an email received from the team of young researchers recently, we were informed that the results of this article have been published in another study (2), which is considered ethical misconduct. This issue was investigated by the editorial team of the Journal of Herbmed Pharmacology. As a result, based on the Committee on Publication Ethics (COPE) guidelines, the editors decided to retract this paper. The authors were informed and advised on this serious ethical breach. This article has been retracted at the request of the corresponding author. The retracted article will remain online to maintain the scholarly record, but it will be watermarked on each page as ‘retracted’. References 1. Jalili C, Abdolmaleki A, Roshankhah S, Salahshoor MR. Histopathological and biomedical parameters determination in the protective effect of crocin on hepatotoxicity induced by methotrexate in rats. J Herbmed Pharmacol. 2020;9(1):48-54. doi: 10.15171/jhp.2020.07. 2. Salahshoor MR, Abdolmaleki A, Jalili C, Roshankhah S, Ziapour A. Determination of histopathological and biomedical parameters in protective effects of Petroselinum crispum on hepatotoxicity induced by dichlorvos in male Wistar rats. Comp Clin Path. 2020;29(2):501-9. doi: 10.1007/s00580-019-03087-7.